2021
DOI: 10.1002/pssr.202100246
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of TiOx‐Based Electron‐Selective Contacts on n‐Type Crystalline Silicon and Solar Cell Efficiency Potential

Abstract: Research data are not shared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
3
7
0
Order By: Relevance
“…Therefore, it is unlikely that the huge decrease of the series resistance is solely caused by increasing the oxygen deficiency of the TiO layer. Indeed, recent studies 20 , 29 on samples with virtually identical selective contact processing conditions to ours showed that the contact resistance of SiO /TiO contacts is much higher compared to TiO ones and almost independent of TiO thickness in the as-deposited state, while for the annealed samples the contact resistances are almost identical and a clear dependence on TiO thickness is observed. This identifies the TiO layer as limiting the contact resistance in the annealed sample, but excludes it for the as-deposited state.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Therefore, it is unlikely that the huge decrease of the series resistance is solely caused by increasing the oxygen deficiency of the TiO layer. Indeed, recent studies 20 , 29 on samples with virtually identical selective contact processing conditions to ours showed that the contact resistance of SiO /TiO contacts is much higher compared to TiO ones and almost independent of TiO thickness in the as-deposited state, while for the annealed samples the contact resistances are almost identical and a clear dependence on TiO thickness is observed. This identifies the TiO layer as limiting the contact resistance in the annealed sample, but excludes it for the as-deposited state.…”
Section: Discussionsupporting
confidence: 70%
“…For data on the passivation quality of the contacts, the reader is referred to Ref. 29 , where passivation data is extensively studied.
Figure 1 Characteristics of the investigated solar cells.
…”
Section: Resultsmentioning
confidence: 99%
“…A similar phenomenon of lifetime recovery was also observed on SiO x /TiO x /Al heterocontacts by Yang et al [ 30 ] and Titova et al [ 24 ] They grew ≈1.2 nm thermal and ≈1.3 nm native SiO x prior to TiO x deposition, respectively. One possible explanation for the recovery of lifetime is its similarity to the well‐known “alneal” process, in which a thin Al layer is evaporated on the SiO 2 passivation layers before annealing.…”
Section: Resultssupporting
confidence: 79%
“…Recently, Titova and Schmidt used the dynamic infrared lifetime mapping technique to investigate the passivation of the fully metalized n ‐Si/SiO x /TiO x /Al heterocontact, demonstrating that the Al electrode resulted in passivation degradation. [ 24 ] To the best of our knowledge, a comprehensive investigation of the impact of metal electrode on the surface passivation of TiO x ‐based heterocontacts is still lacking. We reported some preliminary test results last year in a conference presentation, [ 25 ] based on which this article delivers further comprehensive results and discussion on: 1) a new heterocontact based on non‐doped TiO x , 2) accurate passivation evaluation with derived effective lifetime from PL images, and 3) understanding the passivation deterioration mechanism with XPS, STEM and energy‐dispersive X‐ray spectroscopy (EDX) characterization.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] One of the most studied metal oxides in this context is titanium oxide (TiO x ). [15][16][17][18][19][20] It is successfully applied in organic and dopant-free asymmetric hetero-contact (DASH) silicon solar cells. Due to different stoichiometries, TiO x exhibits a wide range of work functions between 3.8 and 4.4 eV and doping levels between 1E16 and 3E19 cm À3 .…”
Section: Introductionmentioning
confidence: 99%